Development and evaluation of silver amplification immunochromatography kit for foot-and-mouth disease virus antigen detection - Morioka, Kazuki; Urayama, Kana; Wada, Atsuhiko; Yoshida, Kazuo; Kato, Tomoko; Kitano, Rie; Nishi, Tatsuya; Kanno, Toru; Yamada, Manabu; Yamakawa, Makoto; Ulziibat, Gelermaa; Makino, Yoshihiko; et al. (Journal of Virological Methods, 2020)
•A silver amplification immunochromatography was developed for FMDV antigen detection.•FMDV-Ag SAI increased the sensitivity of conventional immunochromatographic assay.•FMDV-Ag SAI was able to detect specific antigen even in saliva samples.•FMDV-Ag SAI was evaluated with various clinical samples from an outbreak. A silver amplification immunochromatography (SAI) kit for the detection of all seven serotypes of foot-and-mouth disease virus (FMDV)—FMDV-Ag SAI—was developed using the monoclonal antibody 1H5 recognizing the highly conserved N terminus region of VP2. The FMDV-Ag SAI can be used under conditions of high biosecurity containment as it does not require any apparatus. The FMDV-Ag SAI exhibited 10–100 times higher sensitivity against the five serotypes (O, A, Asia1, C, and SAT1) and similar sensitivity against SAT2 and SAT3, compared with the Svanodip® FMDV-Ag kit immunochromatography kit. The Svanodip kit showed inhibitory results with several saliva samples but not with the FMDV-Ag SAI kit. In a validation study using clinical samples (n = 132; vesicular epithelium = 92, vesicular lesion swabs = 20, saliva = 20) in Mongolia, the sensitivity of FMDV-Ag SAI in comparison with real-time reverse transcription-polymerase chain reaction revealed the following data: vesicular epithelium, 85.4% (76/89); vesicular lesion swab, 46.7% (7/17); and saliva, 36.8% (7/19). No cross-reactivity with the non-FMDV vesicular-forming viruses and taxonomically related viruses of the Picornaviridae family occurred. The FMDV-Ag SAI is a highly sensitive diagnostic tool that enables pen-side diagnosis without requiring the use of any equipment.